2008
DOI: 10.1111/j.1475-4762.2008.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐level analysis of childhood obesity, diet, physical activity, residential socioeconomic and social capital variables: where are the obesogenic environments in Leeds?

Abstract: This paper describes global (whole of Leeds) and local (super output area) analyses of the relationship between childhood obesity and many 'obesogenic environment' variables, such as deprivation, urbanisation, access to local amenities, and perceived local safety, as well as dietary and physical activity behaviours. The analyses identify the covariates with the strongest relationships with obesity, and highlight variation in these relationships across Leeds, thus identifying 'at-risk' populations. This paper s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…However, public health researchers have begun to challenge the stationarity assumption. Using spatial regression modeling, such as geographically weighted regression (GWR), a technique that allows for spatial variations in parameter estimates (19,20), investigators have highlighted variations in associations across space between a range of environmental exposures and outcomes such as diet (21), obesity (22)(23)(24)(25)(26)(27), active transportation (28), and birth weight (29). Fraser et al (21) have observed marked spatial variations, in both magnitude and nature, in the relationship between residential exposure to fast-food outlets and fast-food consumption among adolescents living in Bristol, United Kingdom.…”
mentioning
confidence: 99%
“…However, public health researchers have begun to challenge the stationarity assumption. Using spatial regression modeling, such as geographically weighted regression (GWR), a technique that allows for spatial variations in parameter estimates (19,20), investigators have highlighted variations in associations across space between a range of environmental exposures and outcomes such as diet (21), obesity (22)(23)(24)(25)(26)(27), active transportation (28), and birth weight (29). Fraser et al (21) have observed marked spatial variations, in both magnitude and nature, in the relationship between residential exposure to fast-food outlets and fast-food consumption among adolescents living in Bristol, United Kingdom.…”
mentioning
confidence: 99%
“…This proportion is displayed for the census dataset, the simulated dataset, and the HSE sub-sample dataset for the Yorkshire and Humber GOR, followed by the differences in these proportions between the different datasets. For example, 48.5% of the people living in the study area according to the Census dataset are male (1) and (2) Differences between (1) and (3) Differences between (2) and (3) Obese n/a 20.8 28.7 n/a n/a 7.9 authors are seeing both effects (Cummins et al 2007;Procter et al 2008). It would be informative to investigate the areas with particularly high (and low) relative risks to seek to determine whether there is something about these areas that impacts the health behaviours of individuals or otherwise results in obesity.…”
Section: Discussionmentioning
confidence: 96%
“…These models have been used to model health data (for example, see Morrissey et al 2008;Procter et al 2008;Tomintz et al 2008). Spatial microsimulation models can provide small area estimates that could be used in a practical way to help to influence policy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The essence of the problem is that many health and lifestyle conditions exhibit demographic profiles which are strongly skewed and richly characterised within surveys like the Health Survey for England and British Household Panel Survey, but none of these provides the spatial detail required for the planning of local services. Through the combination of synthetic individual demographic profiles for small areas, which may be generated from an abundance of Census Area Statistics (Birkin & Clarke 1988;Ballas et al 2005), with health profiles of real but anonymised individuals from survey sources, researchers have been able to estimate local distributions of conditions as diverse as diabetes (Smith 2007), obesity (Procter et al 2008) and smoking (Tomintz et al 2008). In addition to their use as a backdrop for service evaluation (see below), simulated distributions can provide valuable estimates of 'missing data' in their own right.…”
Section: Local Policy Issuesmentioning
confidence: 99%